2010
DOI: 10.1007/s10529-010-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of increasing sugar concentrations on ethanol production from maize or decorticated sorghum mashes fermented with Saccharomyces cerevisiae or Zymomonas mobilis

Abstract: The efficiency of ethanol fermentation, as affected by grain source (maize and decorticated red sorghum), total sugar concentration (13 or 20° Plato) and type of microorganism (Saccharomyces cerevisiae or Zymomonas mobilis) was studied. Maize mashes yielded 0.32 l ethanol kg(-1) ground grain whereas mashes prepared with decorticated red sorghum produced 0.28 l ethanol kg(-1). Both microorganisms yielded similar amounts of ethanol. However, high-gravity mashes (20° Plato) yielded lower amounts of ethanol compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The raw and extruded maize meals were liquefied with thermoresistant α -amylase (Liquozyme SC DS, Novozymes, Bagsvaerd, Denmark) according to previous investigations [ 5 , 18 ]. Then, hydrolyzates were saccharified with amyloglucosidase (Dextrozyme, Novozymes, Bagsvaerd, Denmark) in preparation for fermentation trials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The raw and extruded maize meals were liquefied with thermoresistant α -amylase (Liquozyme SC DS, Novozymes, Bagsvaerd, Denmark) according to previous investigations [ 5 , 18 ]. Then, hydrolyzates were saccharified with amyloglucosidase (Dextrozyme, Novozymes, Bagsvaerd, Denmark) in preparation for fermentation trials.…”
Section: Methodsmentioning
confidence: 99%
“…There is growing interest to develop several new technologies, especially through mechanical, chemical, and biological processes to optimize ethanol produced from maize [ 5 , 6 ]. An interesting approach is the implementation of thermoplastic extrusion, because it modifies starch to dextrose and lowers energy needs for high pressure steam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nitrogen sources such as yeast extract or peptone enhance ethanol production in yeast. 41,42 These nitrogen sources also enhance sugar utilization for increased ethanol yield. [42][43] Yeast extract also supplies cofactors such as biotin and riboflavin for enhancement of ethanol yield.…”
Section: Medium Compositionmentioning
confidence: 99%
“…Recently, more attention has been paid to beer brewing with very high gravity (VHG) wort (18-25°P) due to its greater economic advantages. The VHG brewing can increase production efficiency and capacity, reduces energy, labor and capital costs, as well as improve beer smoothness and haze stability (Cooper et al 1998;Pérez-Carrillo et al 2011). However, yeast cells have to be exposed to higher osmotic stress and ethanol stress during VHG fermentation compared to the normal gravity fermentation (Pereira et al 2010).…”
Section: Introductionmentioning
confidence: 99%